Good Corporate Governance dan Corporate Social Responsibility di Indonesia: Pentingkah Earnings Response Coefficient? - Sujarwati, Rianita; Khoirunisa, Ikasari; Firmansyah, Amrie (Nominal: Barometer Riset Akuntansi dan Manajemen, 2022)
Abstrak: Good Corporate Governance dan Corporate Social Responsibility di Indonesia: Pentingkah Earnings Response Coefficient? Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Good Corporate Governance (GCG) dan pengungkapan Corporate Social Responsibility (CSR) terhadap Earnings Response Coefficient (ERC) pada perusahaan subsektor perbankan yang terdaftar di BEI periode 2017"”2019Data dianalisis dengan metode uji regresi linear berganda untuk data panel. Hasil uji menunjukkan Good Corporate Governance (GCG) berpengaruh positif signifikan terhadap Earnings Response Coefficient (ERC), sedangkan Corporate Social Responsibility (CSR) tidak berpengaruh terhadap Earnings Response Coefficient (ERC). Penelitian ini memberikan gambaran dan informasi terkait kualitas laba perusahaan perbankan yang ditunjukkan dari reaksi investor terhadap pengungkapan good corporate governance dan corporate social responsibility. Berbeda dengan penelitian sebelumnya, penelitian ini menilai pengungkapan Good Corporate Governance (GCG) menggunakan indikator Surat Edaran OJK Nomor 13/SEOJK.03/2017 tentang Penerapan Tata Kelola Bagi Bank Umum.Kata kunci: corporate social responsibility, earnings response coefficient, good corporate governance, unexpected earningsAbstract: Good Corporate Governance and Corporate Social Responsibility in Indonesia: Is the Earnings Response Coefficient Important? This study aims to examine and analyze the effect of Good Corporate Governance (GCG) and disclosure of Corporate Social Responsibility (CSR) on the Earnings Response Coefficient (ERC). This study uses secondary data from banking sub-sector companies listed on the Indonesia Stock Exchange during 2017-2019. The data were analyzed using the multiple linear regression test method for panel data. The test results indicate that Good Corporate Governance (GCG) has significant positive effect on the Earnings Response Coefficient (ERC), while the Corporate Social Responsibility (CSR) does not affect the Earnings Response Coefficient (ERC). This study provides an overview and information related to the earnings quality of banking companies as indicated by investor reactions to the disclosure of GCG and CSR. In contrast to previous research, this study assesses the disclosure of Good Corporate Governance (GCG) using the indicators of the Circular Letter of The Financial Services Authority Number 13/SEOJK.03/2017 concerning the Application of Good Corporate Governance for Commercial Banks. Keywords: corporate social responsibility, earnings response coefficient, good corporate governance, unexpected earnings